VO#059 The quotation for 77.93 mm thick patent stone over average thickness of 50mm - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the quotation for 77.93 mm thick patent stone over average thickness of 50mm for BRACU new campus project.